A Study of the Islamic Feminists' Perception of Good Governance - Amir mohammad Haji yousefi; Fahimeh Azmoudeh; Reza Khorasani (رهیافتهای سیاسی و بین المللی)
The present article first examines the views of Islamic feminists such as Mernissi, Ahmad and Al-Hibri on good governance, and then examines their ideas from the perspective of the official Islam. Islamic feminism is part of the current course of modernism in the Islamic world. In their view, Islamic laws that prevent the presence of women in the community have a historical nature. From the Islamic feminists' perspective, Islamic laws have degraded the indicators of good governance in Islamic countries, so they believe that by re-interpreting the Islamic text, conditions can be found for changing many Islamic laws regarding women's affairs. For this reason, we are trying to review and critique the concept of Islamic feminism of good governance. According to this study, their perception of good governance suggests a lack of attention to cultural grounds. Using discourse analysis methodology, this article tries to review the works of the three of the most prominent theorists in this field from the official Islamist viewpoint. Ultimately, the process of facilitating good governance in Iran is expressed in the light of the official Islam.